A Review of the Catalytic Mechanism of Human Manganese Superoxide Dismutase - Jahaun Azadmanesh; Gloria E. O. Borgstahl (MDPI AG, 2018)
Superoxide dismutases (SODs) are necessary antioxidant enzymes that protect cells from reactive oxygen species (ROS). Decreased levels of SODs or mutations that affect their catalytic activity have serious phenotypic consequences. SODs perform their bio-protective role by converting superoxide into oxygen and hydrogen peroxide by cyclic oxidation and reduction reactions with the active site metal. Mutations of SODs can cause cancer of the lung, colon, and lymphatic system, as well as neurodegenerative diseases such as Parkinson's disease and amyotrophic lateral sclerosis. While SODs have proven to be of significant biological importance since their discovery in 1968, the mechanistic nature of their catalytic function remains elusive. Extensive investigations with a multitude of approaches have tried to unveil the catalytic workings of SODs, but experimental limitations have impeded direct observations of the mechanism. Here, we focus on human MnSOD, the most significant enzyme in protecting against ROS in the human body. Human MnSOD resides in the mitochondrial matrix, the location of up to 90% of cellular ROS generation. We review the current knowledge of the MnSOD enzymatic mechanism and ongoing studies into solving the remaining mysteries.